2017
DOI: 10.1186/s12958-017-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cervix tissue homogeneity by ultrasound elastography in infertile women for the prediction of embryo transfer ease: a diagnostic accuracy study

Abstract: BackgroundUltrasound elastography is a non-invasive medical imaging technique able to quantitatively characterize the stiffness of a given tissue. It has been shown to predict the risk for cervical insufficiency and preterm delivery, and to allow differentiation of malignancy from normal tissue. The present study sought to evaluate whether cervical tissue dishomogeneity, as assessed by cervical ultrasound elastography, may predict the embryo transfer (ET) ease in infertile women undergoing IVF/ICSI.MethodsWe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Appropriate elastosonography image quality was confirmed by the absence of artifacts, when the elastogram and B-mode ultrasound images matched and a green spring was produced, representing a real-time feedback of accurate image acquisition as previously reported. 23,24 The elastosonography images were evaluated post-processing and the borders of the patellar ligament were manually drawn in the B-mode image, while being simultaneously copied onto the elastosonography image (►Fig. 2), thus making the visible portion of the patellar ligament the region or interest.…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate elastosonography image quality was confirmed by the absence of artifacts, when the elastogram and B-mode ultrasound images matched and a green spring was produced, representing a real-time feedback of accurate image acquisition as previously reported. 23,24 The elastosonography images were evaluated post-processing and the borders of the patellar ligament were manually drawn in the B-mode image, while being simultaneously copied onto the elastosonography image (►Fig. 2), thus making the visible portion of the patellar ligament the region or interest.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some physicians have used this new tool to assess cervical lesions. [13] Stanziano et al [14] found that cervical ultrasound elastography, by identifying cervical tissue inhomogeneity, may be helpful to predict embryo transfer ease in infertile women candidates to embryo transfer or intracytoplasmic sperm injection. Many radiologists or obstetricians have applied this technique to predict labor induction success.…”
Section: Introductionmentioning
confidence: 99%
“…ET can be complicated by tortuosity and/or stenosis of the cervical canal. In contrast to OH, cervical ultrasound elastography is less effective in predicting the ease of ET [ 32 ], and our results suggested that ultrasound was less effective in predicting cervical lesions.…”
Section: Discussionmentioning
confidence: 85%